THE INTENTION TO USE E-GOVERNMENT SYSTEM (E-EXPORTING) IN SHIPPING AND EXPORTING COMPANY IN LIBYA - Jubran, Dhwo; Djamhuri, Ali; Baridwan, Zaki (Accounting Department,, 2016)
Recently, many countries, either developing or developed, concern about the e-government as a new project. They took it in their account by paying more attention about this project. This paper was conducted in a shipping and exporting company by distributing questionnaires over 110 finance and admission employees. It employs TAM’s and UTAUT’s model to determine the main factors influencing the intention to use E-government system. The factors being on account are perceived usefulness, perceived ease of use, trust, and awareness. Their correlations with the dependent variable (intention to use e-government) have been examined. The researcher added two moderating variables (Age & Experience) to investigate their impact on the direct relationship between the independent and dependent variables. However, government considers that there is remarkable lack of acceptance on the new system which includes e-government from the employees, even the whole citizens. This problem is faced by the Libyan government. Thus, this paper tried to find the causes behind the lack of acceptance of the employees upon the new system. The results obtained are reliable enough for the use of statistical tool which is PLS program that is derived from SEM. For instance, the obtained result demonstrates that the perceived usefulness has the non-significant relationship but the perceived ease of use; trust and awareness have significant relationship toward intention to use E-government system.